Physical Therapist Practice in the Emergency Department: From Innovation to an Emerging Standard of Care - Stacie Fruth; Kelsie Clark; Kevin E. Brueilly (Journal of Acute Care Physical Therapy, 2026)
ABSTRACT Purpose/Introduction: U.S. Emergency departments (EDs) face challenges related to patient volume, wait times, and resource utilization. Although physical therapists (PTs) are increasingly integrated into ED settings, the characteristics of this specialty practice remain widely unknown. Existing literature demonstrates that PT involvement in EDs can positively impact wait times, length of stay, imaging use, hospital admissions, and patient satisfaction. However, how PTs are currently utilized within U.S. EDs remains poorly understood. The purpose of this study was to provide an in-depth exploration and analysis of PT practice in U.S. EDs. Methods: A cross-sectional observational study was conducted using a convenience sample of PTs practicing in U.S. EDs. Data were collected via a 47-item web-based survey and analyzed using descriptive statistics and chi-square analyses. Qualitative responses were analyzed using thematic analysis. Results: Seventy-nine participants completed the survey with 55 reporting at least 15 hours/week of ED practice. Findings demonstrated variability in practice models, referral processes, and scope of practice. PTs most frequently managed musculoskeletal, balance/fall, and vestibular conditions and reported high confidence in performing components of medical screening examinations. Strong interprofessional collaboration was reported, although barriers included underutilization and limited understanding of PT knowledge and skills. Respondents expressed support for expanded practice privileges, including imaging and independent management of low-acuity conditions. Conclusion: PT practice in U.S. EDs is an evolving and variable specialty area. PTs are highly involved in patient care and are valued members of the ED provider team. These findings provide foundational insight to support future standardization, education, and research to optimized ED PT practice.